AWARENESS OF MEDICAL ETHICS PRINCIPLES AND THEIR APPLICATIONS AMONG HEALTHCARE PROFESSIONALS IN PAKISTAN - Wasfa Farooq; Amenah Jafarey; Aleena Arshad (ziauddin University, 2019)
Background: The importance of medical ethics principles is not emphasized therefore has diminished role in the medical students' mind. Additionally, practicing in an environment where senior physicians and consultants are not seen prioritizing moral ethical values in their clinical practice, creates an air of indifference. This study was done to assess the awareness of HEC defined objectives for Medical Ethics in the medical curriculum, along with gauging the understanding of key Medical Ethics concepts by way of multiple choice clinical scenarios. Methods: This is a cross-sectional study conducted over three months. Response forms were filled at a private and government hospital. The sample size of 243 subjects was finalized according to the number of available House Officers and Postgraduate trainees. The questionnaire was aimed purely at MBBS graduates from Pakistan. Results: A total of 243 responses were collected, ranging from House Officer level doctors 139(57%) up to Postgraduate level 104(43%). Analysis was done to determine association of awareness of Medical Ethics objectives with their medical school background. Ethical concepts of Confidentiality, Non-malefaience, Informed Consent, Respect for Privacy and Desirable Attitudes in Healthcare Professionals showed significant p-values of 0.006, 0.016, 0.005, 0.013 and 0.045. The number of incorrect responses to the clinical scenarios were: 55(25.3%), 111(51.4%), 87(42%), 119(55.3%), 104(47.9%), 170(78.7%), 50(23.4%). There was no significant difference in response among graduates from different backgrounds or with different years of clinical experience. Conclusion: A significant disconnect exists in the application of the knowledge of medical ethics in the clinical setting with several factors affecting physician judgment in ethical dilemmas. Effective teaching and assessment methods, inclusion of postgraduate ethical courses along with a regulatory ethics committee in each hospital is needed to protect both doctors and patients.